DIGITAL LITERACY IN THE TRANSFORMATION OF HISTORICAL LEARNING IN THE TIME OF COVID-19 - Fitri Mardiani; Mohamad Zaenal Arifin Anis; Muhammad Dody Hermawan (JURNAL SOCIUS, 2021)
Abstract Change layout: how to learn and learn the history that occurred due to the Covid-19 pandemic that hit almost all over the world, especially in the field of education and learning history in the department of history of education FKIP ULM. In addition to the challenges of the times, global change is increasingly urgent because of a transformation in the education system and learning in Indonesia. In accordance with the demands that we should be able to survive in the midst of the complexity of the challenge and complexity of life in the pandemic. Digital technologies continue to evolve into an integral part in the education world additionally traffic digital literacy to be an ability that must be possessed to be able to explore the information, the message and also process them with good so right on target. This research uses descriptive qualitative research methods, analyzing the extent to which the understanding related to digital literacy in the transformation of learning the history of the covid-19 in the online learning of History of Education Department of FKIP ULM